Modelagem estrutural de dolfins de atracação de navios através da análise modal operacional - Henrique, Thiago (2019)
Ambient Vibration Analyses is a non-destructive structural investigation based only on the operation and ambient actions as a source of excitation. The advantage of this methodology is the possibility of conducting vibration measurements of the structure without paralyzing its functionality. Considering the accelerations recorded over time, signal processing techniques were used in the frequency domain to obtain the modal parameters of the structure, such as: natural frequencies, vibration modes and damping rates. Accelerometers were installed to capture the main vibration modes of dolphins on a pier where bulk vessels up to 450,000 tons are berthed. Each dolfim is composed of a set of piles with a superior reinforced concrete block. From the comparison between actual measured and numerical parameters obtained from a model based on the finite element method and structural design data, it was possible to perform the calibration of a numerical modelling of the dolfins from the adaptation of the numerical model to the values obtained in the field. Thus, the overall imperfections and damages existing in the structure were properly considered. The result of the experiment was the numerical characterization of the structure, as well as a structural analysis of the results aiming to compare the damage levels on each structure. The dolphin that receives the first impact of vessels during the berth maneuvering has decreased its original stiffness by 10% and the mooring dolphin analyses indicated a serious damage on its piles.